The TRIPS Flexibilities and the Patent Law of Pakistan: A Comparative Study - Butt, Saima; Akhter, Noreen (Annals of Human and Social Sciences, 2023)
The WTO agreement on trade related aspects of intellectual property rights (TRIPS Agreement) results in the global implementation of intellectual property (IP). Global implementation of IP and particularly the protection of pharmaceutical patents apprehend that it will affect the public health and affordability of patented medicines. To overcome this issue, the TRIPS Agreement provides a range of flexibilities to ensure public health. This article analysed the provisions of Patent Ordinance 2000 of Pakistan dealing with parallel importation and compulsory licensing. The object of this study is to investigate to what extent the flexibilities provided by the TRIPS agreement has been incorporated into Pakistan’s patent legislation. The methodology applied for this research is primarily comparative and bears the qualitative aspect of the issue. This research concludes that the Patent Ordinance of Pakistan fails to incorporate adequate provision of parallel importation and compulsory licensing according to the needs of its people and local industry. Accordingly, this research suggests that there is a dire need to amend the Patent Ordinance of Pakistan to make it more workable and practical.